Relasi Uang dan Kekuasaan dalam Konteks Pertukaran Sosial dan Dominasi Impersonal - Eka S Saputra; Herdito Sandi Pratama (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Abstract: This article discusses social exchange in the relationship between money and power, where money as an economic medium can direct power politically. The framework of thought used refers to Karl Marx. However, this research puts forward a method of critical thinking analysis, with a new approach to reading Marx as pioneered by the Frankfurt School. The steps taken include investigation, interpretation, and deliberation within the framework of a qualitative study. As a result, it appears that there is a development of Marx's theory of value from originally related to concrete work to be intertwined with abstract work through the mediation of money. This research also finds that the tangled threads of social exchange in relation to money and power are formed through fetishism. The worship of money as an independent value binds the existence of value to the form of money. This then manifests impersonal domination. Prioritization of money occurs at the expense or neglect of social relationships and human values. To overcome this tangle, it is necessary to reject the logic of capital, which makes everything rely on money.Fundamentally, this rejection refers to universal, particular, and singular frames in Žižek's review. Within this framework, the rejection of singular, specific individuals or groups, particularly operative organizational programs, and protest movements with broad universal alliances must work together to drive change.Keywords: Money, Power, Karl Marx, Social Exchange, Fetishism.